Electrónico” Funcimat” Como Herramienta Didáctica Para El Estudio De Funciones Matemáticas Y Su Incidencia En El Rendimiento Académico Estudio De Caso: Escuela De Agronomía, Facultad De Recursos Naturales Espoch - Arellano, Marco Hjalmar Velasco; Guadalupe, Carla Sofía Arguello; Mena, Mayra Mayra Elizabeth Caceres; Torres, José Franklin Arcos; Murillo, Patricia del Lourdes Gallegos (European Scientific Journal, ESJ, 2017)
This research work shows a comparative study between using and not using the electronic module called Funcimat and its incidence in the students’ academic performance. The students who were considered for this experiment belonged to the first semester of the Agronomy School. This group, which was divided in two, served as the experiment and the control samples. The experiment was based on the teaching – learning process of Mathematics. Funcimat was applied to one group, and the traditional methodology and techniques were applied to the other group. In order to demonstrate the hypothesis, the Chi squared test was applied to see the difference of proportions and correlation since the idea is to compare Funcimat incidence on the academic performance. The results obtained before and after the experiment determined that there are significant differences between the traditional methodology and the alternative guidelines. Funcimat allows the students to build their own reasoning scenario about mathematical reasoning. This way they develop knowledge and skills to solve each one of the proposed mathematical functions.